Multipolarism and cosmopolitanism. Beyond the double standard metropolis/colonies - Grimaldi, Giorgio (Itinerari, 2023)
The current international framework is characterised by the fading of one world superpower and the formation of various centres of power; that is, a multipolar structure of world order. Will these Great Spaces prelude an acceleration of an historical movement toward Cosmopolitanism? Alternatively, will they establish closed political spaces in perpetual conflict or in an unstable balance of power? Much depends on overcoming the double standard metropolis/colonies – a longstanding political pattern that can take on different shapes.